Foliage est-il à leaves ce que jewellery est à jewels ? Etude de rapports entre dénombrables au pluriel et indénombrables singuliers - Laure Gardelle (Anglophonia)
Existing research on the nouns that denote pluralities of units has isolated a category of nouns that denote heterogeneous aggregates (such as jewellery or furniture). The present paper seeks to establish whether the category of “aggregates” should be extended to nouns such as foliage, which are not mentioned in studies. Like jewellery or furniture, they only have non-count uses; but they do not apply to heterogeneous units, and are therefore not hyperonymic (at least in their central sense). The study concludes that hetereogeneity is not a defining feature of aggregate nouns, and that nouns of the foliage type should be included. Like the other non-count nouns studied here, they construe the units as parts of a whole (unlike the “groupings” denoted by N + ‑s, in which reduplicated units can be compared and differentiated within the set, and allow access to their parts). They also differ from collective nouns, which are count nouns, in that a distributive property cannot be ascribed to the set (heart-shaped foliage / jewellery, for instance, has to describe the shape of the individual leaves or jewels). Like the nouns that denote aggregates of heterogeneous units, nouns of the foliage type exist because they foreground the common function of the units, to the detriment of their individuality.Foliage type nouns differ from nouns that denote heterogeneous aggregates in one major respect, beyond the lack of heterogeneity: the units are construed as being fixed on a support (typically a branch, or branches, for foliage). This explains why a piece of foliage may not denote a leaf, where a piece of jewellery typically refers to a jewel. But the study concludes that this feature does not exclude foliage nouns from the category of aggregate nouns; similarly, collective nouns exhibit a broad range of variations in their behaviour and conceptualisation.